Fumigation of three major soil pests (Agriotes lineatus, Diabrotica virgifera virgifera, Phyllopertha horticola) with 3-octanone and 1-octen-3-ol enantiomers. Issue 7 (3rd July 2022) - Bourdon, Pierre-Antoine; Zottele, Maria; Baxter, Ian; Myrta, Arben; Midthassel, Audun; Wechselberger, Katharina F.; Khoja, Salim; Bull, James C.; Hermann, Strasser; Butt, Tariq M.
ABSTRACT: New pest management solutions are needed to control soil invertebrates (insects, nematodes, mollusks) in order to implement the goals of the European Green Deal. Natural volatile organic compounds (VOCs) such as 1-octen-3-ol and 3-octanone, emitted by the entomopathogenic fungus Metarhizium brunneum could be part of the solution. Three major crop pests, Agriotes lineatus (wireworm), Diabrotica virgifera virgifera (corn rootworm) and Phyllopertha horticola (garden chafer), were susceptible to fumigation with 1-octen-3-ol and 3-octanone. The toxicity of the VOCs was tested in soil-free arenas and in soils which differed in moisture content and porosity. The mortality rates were dependent on the interaction between the VOC treatment, dose and pest species. The insects differed in their sensitivity to these VOCs. A dose of 1.25 µl of 1-octen-3-ol applied in a closed glass tube was sufficient to kill D. v. virgifera and P. horticola in soil trials whereas 5 µl was needed to kill A. lineatus . The highest dose (20 µl) was highly toxic to all insects. Soil moisture content slightly influenced mortality rates whereas porosity had no obvious impact. The mode of action of the VOCs is unknown but the compounds are likely to cause tissue damage and loss of body fluids. This may explain the shrivelled appearance of corn rootworm and garden chafer and melanisation in wireworm. Both 1-octen-3-ol and 3-octanone show promise as biofumigants.